Oligohydramnios affects pulmonary functional/structural abnormalities in school-aged children with bronchopulmonary dysplasia - Jeong Eun Shin; Soon Min Lee; Mi-Jung Lee; Jungho Han; Joohee Lim; Haerin Jang; Ho Seon Eun; Min Soo Park; Soo Yeon Kim; Myung Hyun Sohn; Ji Ye Jung; Kyung Won Kim (The Korean Pediatric Society, 2024)
Background The relationship between early life factors and childhood pulmonary function and structure in preterm infants remains unclear. Purpose This study investigated the impact of bronchopulmonary dysplasia (BPD) and perinatal factors on childhood pulmonary function and structure. Methods This longitudinal cohort study included preterm participants aged ≥5 years born between 2005 and 2015. The children were grouped by BPD severity according to National Institutes of Health criteria. Pulmonary function tests (PFTs) were performed using spirometry. Chest computed tomography (CT) scans were obtained and scored for hyperaeration or parenchymal lesions. PFT results and chest CT scores were analyzed with perinatal factors. Results A total 150 children (66 females) aged 7.7 years (6.4-9.9 years) were categorized into non/mild BPD (n=68), moderate BPD (n=39), and severe BPD (n=43) groups. The median z score for forced expiratory volume in 1 second (FEV1), forced vital capacity (FVC), FEV1/FVC ratio, and forced midexpiratory flow (FEF25%-75%) were significantly lower in the severe versus non/mild BPD group (-1.24 vs. -0.18, -0.22 vs. 0.41, -1.80 vs. -1.12, and -1.88 vs. -1.00, respectively; all P<0.05). The median z scores of FEV1, FEV1/ FVC, and FEF25%-75% among asymptomatic patients were also significantly lower in the severe versus non/mild BPD group (-0.82 vs. 0.09, -1.68 vs. -0.87, -1.59 vs. -0.61, respectively; all P<0.05). The severe BPD group had a higher median (range) CT score than the non/mild BPD group (6 [0-12] vs. 1 [0-10], P<0.001). Prenatal oligohydramnios was strongly associated with both low pulmonary function (FEV1/FVC<lower limit of normal; odds ratio, 3.54) and high CT score (median difference, 2.54). Conclusion School-aged children with severe BPD showed airflow limitations and structural abnormalities despite no subjective respiratory symptoms. These results suggest that patients with a history of prenatal oligohydramnios or prolonged mechanical ventilation require extended follow-up.